Home schooling during the COVID-19 pandemic in the United Kingdom: The experience of families of children with neurodevelopmental conditions - Kouroupa, Athanasia; Allard, Amanda; Gray, Kylie M.; Hastings, Richard P.; Heyne, David; Melvin, Glenn A.; Tonge, Bruce J.; Totsika, Vasiliki (Frontiers in Education, 2022)
The COVID-19 outbreak, and associated school restrictions affected the learning experience of students worldwide. The current study focused on the learning experiences of UK children with neurodevelopmental conditions, including autism and/or intellectual disability. Specifically, the aim was to examine families’ experience with school support for home schooling, families’ resources, and level of satisfaction with schools among families whose children engaged with home schooling, hybrid learning, and school-based learning during the pandemic. An online survey took place in 2021, approximately one year since the start of the COVID-19 pandemic in the UK. Participants were recruited mostly through social media with support via several charities across the UK. Participants were 809 parents/carers of children with autism and/or intellectual disability aged 5 – 15 years. Of these, 59% were learning from home daily during home schooling, 19% spent some days in school (hybrid learning), and 22% were going to school daily during school restrictions. Parents/carers reported on the support received from schools, the resources accessed, and the resources needed but not accessed to facilitate learning. They also reported on their level of satisfaction with school support and school management of COVID-19 risks. Results indicated that learning during the COVID-19 pandemic was mostly via school-provided worksheets, in the home and hybrid learning group. Families had access to the internet/data and a laptop, computer, or tablet to facilitate learning. However, in both learning groups (i.e., home and hybrid learning) they needed but did not have access to special equipment, special software, and a printer. Importantly, 11% of families in home and hybrid learning groups reported not having access to a desk/table. Satisfaction with school support was low in the home and hybrid learning groups. Satisfaction with COVID-19 management was higher for families of children attending school daily (i.e., the school-based learning group). Future education policy decisions during public health crises should take into consideration the needs of children with neurodevelopmental conditions including autism and/or intellectual disability.